Periodontal clinical features of bronchial asthma patient using inhalation drugs - Ginting, Maria Efrinta; Wihardja, Rosiliwati; Carolina, Dyah Nindita (Universitas Padjadjaran, 2021)
Introduction: Bronchial asthma patients use inhalation drugs as therapy to achieve a controlled asthma state. Inhaled corticosteroids and β2 agonists are the medication that is being used in this case. Prolonged use of inhalation drugs will affect the health of periodontal tissue. The effect of these drugs can reduce the periodontal defense mechanism and increase the risk of periodontal disease. This study aims to determine the periodontal clinical features of bronchial asthma patients using inhalation drugs. Method: This research was a descriptive study. The sample of the study were 22 females and 8 males bronchial asthma patients at the Community Lung Health Center of Bandung (Balai Besar Kesehatan Paru Masyarakat Bandung/BBKPM Bandung) who had been using inhalation drugs for at least one year. The periodontal clinical feature was assessed by employing a Community Periodontal Index (CPI) modified with probing the gingival sulcus to assess the presence of gingival bleeding, periodontal pocket, and loss of clinical attachment where then a periodontal status was obtained. The periodontal status data were then processed using the periodontitis case definitions from the Centers for Disease Control and Prevention/American Academy of Periodontology (CDC/AAP) to determine periodontal disease in asthmatics patients. Results: Clinical features of gingival bleeding were found in 26 asthmatic patients (86.7%), periodontal pockets in 18 asthmatic patients (60%), and loss of clinical attachment in 27 asthmatic patients (90%). Based on the CDC/AAP case definition, 23 asthmatic patients (76.7%) had periodontitis. Bronchial asthma patients who used inhalation drugs had a risk of periodontitis.Conclusion: Bronchial asthma patients who used inhalation drugs for at least one year had gingival bleeding and loss of clinical attachment and periodontal pocket.